Proposta metodológica de ensino de biologia da educação numa abordagem dialético-construtivista - Castro, Ronaldo Souza de (1993)
A methodological teaching proposal is the aim of this study. To its development we go over the history of sciences wi th the purpose of clarifyng the present si tuation of the biological epistemology and Educational Biology, consequently. The biological epistemology is analysed aiming the overcoming of càrtesian rationality. Such rationality is elucidated through a historical analysis of the currents existent in biological thought, which allow us to realize the influence of posi ti vism on the logic which is present in this science. We suggest a systematic, holistic and dialectical paradigm, that provides a whole view of this knowledge field, in opposition to positivist and cartesian view, which is still present in Biology. The study of knowledge construction is done as a support of an elaboration of a constructivist proposal of teaching, which is developed in a Federal Institution of Superíor Teaching. Simultaneously, observations take place in other two uni versi ties, aiming the analysis of methodological procedures of teaching. According to the dialectical-construcionism, the teaching proposed succeeds and we suggest the profound theorical analysis of construtivism and a wide debate on the Educational Biology based on the biological epistemology.